The Impact of Pandemic Crisis on the Survival of Construction Industry: A Case of COVID-19 - Gamil, Yaser; Alhagar, Abdulsalam (Richtmann Publishing, 2020)
Since the World Health Organization (WHO) announced the coronavirus 2019 (COVID-19) outbreak as a pandemic, many countries have declared a complete national lockdown after a remarkable spike in COVID 19 cases. These decisions have restricted the movement of people and resulted in a complete shutdown of many businesses across many sectors. The construction industry, as a significant growth driver of the economy with no exception, has also been completely shut down. All the developments and projects were postponed until further notice. It is, therefore, a prudent to address the impact of the pandemic at the outset and end of the crisis to prepare for any future possibility and gain lessons for plans. This study aims to investigate the effect of COVID 19 on the construction industry's survival. The impacts and fallout have been determined and evaluated through the recruitment of construction experts and practitioners. The impacts have been classified into different groups which include economic, human resources. The study implied two methods include exploratory interviews and questionnaire surveys. The study found the most prominent impacts of COVID 19 are the suspension of projects, labour impact and job loss, time overrun, cost overrun, and financial implications. The findings of this study shed light on the consequences of the sudden occurrence of pandemic and raise awareness of the most critical impacts which can’t be overlooked. The findings also help project stakeholders to realise the sequences of the sudden epidemic and prepare for the worst-case scenario during the planning stage of the construction projects.